Analysis of Culture-Specific Translation Strategies Applied to German Translation of Myanmar Short Stories - Khaing, Ei Ei (Journal of Letters, 2018)
Literary translation requires an understanding of cultural context: norms, behavior and cultural values. Translating culture-specific items from literary texts is therefore a very challenging task. The present paper explores translation strategies used in the transfer from Burmese into German of the book Myanmar erzählt: 25 zeitgenössiche Kurzgeschichten (25 Myanmar contemporary short stories) by Klaus R. Schröder und Georg Noack (2008), with a focus on the culture-specific challenges of translation. First, theories of translation are explained, then cultural specificity, culture-specific translation problems and strategies in culture-specific translation are described. To conclude, the applied translation strategies are explored, arranged and analyzed. Results show that direct translation and paraphrasing were the most frequently used strategies, while omission, semantic adaptation and functional equivalence were also used.